Correlation between elastic energy stored in an eye and visual field progression in glaucoma. - Shuichiro Aoki; Hiroshi Murata; Shunsuke Nakakura; Yoshitaka Nakao; Masato Matsuura; Yoshiaki Kiuchi; Ryo Asaoka (PLoS ONE, 2018)
PURPOSE:To investigate whether the elastic energy stored in an eyeball at highest concavity (highest concavity energy; HCE), calculated with Corivs ST (CST, OCULUS), correlates with glaucomatous visual field (VF) progression. METHODS:108 eyes from 70 primary open angle-glaucoma patients were studied. The HCE was calculated using CST parameters. For each eye, the mean total deviation (mTD) of the 52 test points in the 24-2 Humphrey Field Analyzer test pattern was calculated and the mTD progression rate was determined from eight reliable VFs. Eyes were subdivided into: subgroups with low- or high-whole eye motion maximal length (WEM-d) and subgroups with short- or long-time taken to reach WEM-d (WEM-t), as measured with CST. The associations between mTD progression rate and HCE and other ocular/systemic parameters including age, Goldmann applanation tonometry based-intraocular pressure [GAT-IOP], and corneal hysteresis [CH] from the Ocular Response Analyzer (ORA®, Reichert) were investigated using the linear mixed model. The optimal model to describe mTD progression rate was selected from all possible combinations according to the second order bias corrected Akaike Information Criterion index. RESULTS:Optimal models to describe mTD progression rate included: CH in the model for all eyes, age and HCE in the model for the WEM-d low group, HCE in the model for the WEM-t short group, mean GAT-IOP in the model for the WEM-d high group, and age in the model for the WEM-t long-group. CONCLUSIONS:HCE was associated with glaucomatous VF progression in eyes with minimal whole eye motion (low WEM-d and WEM-t subgroups).